Implications of China's innovation policy shift: Does “indigenous” mean closed? - Sebastian Losacker; Ingo Liefner (Growth and Change, 2020)
China's government aims to become an innovation nation and promotes the development of so-called indigenous innovation. Under this paradigm of state-encouraged innovation, however, it is unclear how domestic firms organize their innovation processes. We distinguish between two strategies in that respect: closed versus open innovation. Our findings suggest that firms with closed innovation processes collaborate in close geographic distance, rely on DUI-modes of learning, and collaborations are based on guanxi. In contrast, firms with open innovation processes collaborate over large distances and rely on STI-modes of learning that are not necessarily guanxi-based. The findings help to understand the heterogeneous nature of indigenous innovation in China.
Keywords: 300